The use of nomograms in LDR-HDR prostate brachytherapy - Pujades, Ma Carmen; Camacho, Cristina; Perez-Calatayud, Jose; Richart, José; Gimeno, Jose; Lliso, Françoise; Carmona, Vicente; Ballester, Facundo; Crispín, Vicente; Rodríguez, Silvia; Tormo, Alejandro (Journal of Contemporary Brachytherapy, 2011)
Purpose: The common use of nomograms in Low Dose Rate (LDR) permanent prostate brachytherapy (BT) allows to estimate the number of seeds required for an implant. Independent dosimetry verification is recommended for each clinical dosimetry in BT. Also, nomograms can be useful for dose calculation quality assurance and they could be adapted to High Dose Rate (HDR). This work sets nomograms for LDR and HDR prostate-BT implants, which are applied to three different institutions that use different implant techniques. Material and methods : Patients treated throughout 2010 till April 2011 were considered for this study. This example was chosen to be the representative of the latest implant techniques and to ensure consistency in the planning. A sufficient number of cases for both BT modalities, prescription dose and different work methodology (depending on the institution) were taken into account. The specific nomograms were built using the correlation between the prostate volume and some characteristic parameters of each BT modality, such as the source Air Kerma Strength, number of implanted seeds in LDR or total radiation time in HDR. Results : For each institution and BT modality, nomograms normalized to the prescribed dose were obtained and fitted to a linear function. The parameters of the adjustment show a good agreement between data and the fitting. It should be noted that for each institution these linear function parameters are different, indicating that each centre should construct its own nomograms. Conclusions : Nomograms for LDR and HDR prostate brachytherapy are simple quality assurance tools, specific for each institution. Nevertheless, their use should be complementary to the necessary independent verification.